Rhodopsin mutations in a Scottish retinitis pigmentosa population, including a novel splice site mutation in intron four. Issue 12 (December 1994) - Bell, C; Converse, C A; Hammer, H M; Osborne, A; Haites, N E
Abstract : Retinitis pigmentosa (RP) is the name given to a group of disorders, both clinically and genetically heterogeneous, that primarily affect the photoreceptor function of the eye. Mutations in the genes encoding for rhodopsin, RDS-peripherin, or the beta subunit of the cGMP phosphodiesterase enzyme can be responsible for the phenotype. In this study the rhodopsin gene has been screened for mutations in a panel of RP individuals and five different sequence changes have been detected to date in three dominantly inherited and two unclassified families. One of these, a base substitution in the 3'UTR, has not yet been confirmed as disease specific, while three missense substitutions have previously been reported and are likely to be responsible for the phenotype. The fifth change, a base substitution at the intron 4 acceptor splice site, represents a novel mutation and is assumed to be the causative mutation.